Effect of Platelet-Rich Plasma (PRP) in Combination with Endometrial Scratching for Patients Undergoing Assisted Reproductive Technology Treatment - Krushnali S. Kadu; Akash More; Jarul Shrivastava; Gauri Gajabe; Prerana Dagwar; Namrata Chaudhary; Ritesh Jadhav (Wolters Kluwer Medknow Publications, 2024)
Endometrium scratching is a process of intentionally injuring the endometrium, and after scratching the endometrium, platelet-rich plasma (PRP) is inserted into the endometrial wall to improve pregnancy outcome. This case report revolves around a 33-year-old woman and her 38-year-old husband, who have been married for 3 years and were seeking treatment for their secondary infertility. The female had a history of hypothyroidism, and after the investigation, she was diagnosed with hyperprolactinemia. She also had a history of failure in vitro fertilization (IVF) cycles and two recurrent miscarriages upon investigation. The husband was found to have asthanozoospermia. After diagnosis of the female, we started treatment of cabergoline for hyperprolactinemia, a history of unsuccessful IVF cycles, and two recurrent miscarriages upon investigation. After the treatment of hyperprolactinemia in our clinic, we scheduled ovum pick-up and started the stimulation and performed intra-cytoplasmic sperm injection. After 1 month, we scheduled embryo transfer. On day 1, the progesterone scratched the endometrium wall and loaded the PRP to enhance the endometrial wall, and after an interval of 14 days, we checked the β-hCG level in the blood, and the result was positive, that is, the level was 1020 mIU/mL. The successful result of endometrial scratching with PRP improves pregnancy outcomes.